An educate, test, and treat programme towards elimination of hepatitis C infection in Egypt: a community-based demonstration project. (November 2018) - Shiha, Gamal; Metwally, Ammal M; Soliman, Reham; Elbasiony, Mohamed; Mikhail, Nabiel N H; Easterbrook, Philippa
Summary: Background: Egypt has one of the highest prevalences and burdens of hepatitis C virus (HCV) worldwide, and a large government treatment programme. However, identifying and treating people who are infected in rural communities can be a substantial challenge. We designed and evaluated a comprehensive community-led outreach programme for prevention, testing, and treatment of HCV infection in one village in northern Egypt, with the goal to eliminate HCV infection from all adult villagers, and as a model for potential adoption in rural settings. Methods: A community-based education and test-and-treat project was established in Al-Othmanya village. The programme consisted of community mobilisation facilitated by a network of village promoters and establishment of partnerships; an educational campaign to raise awareness and promote behavioural changes; fundraising for public donations in the local community; and comprehensive testing, diagnosis, and treatment. For the educational campaign, we used public awareness events, house-to-house visits, and promotional materials (eg, booklets, cartoons, songs) to raise awareness of HCV and its transmission, and changes in knowledge, attitudes, and practices were measured through the use of a survey done before and after the educational campaign. Comprehensive testing, linkage to care, and treatment was offered to all eligible villagers (ie, those aged 12–80 years who had not previously been treated for HCV). Testing was done by use of HCV antibody and hepatitis B surface antigen (HBsAg) rapid diagnostic tests, with HCV-RNA PCR confirmation of positive cases, and staging of liver disease by use of transient elastography. HCV-RNA-positive participants were offered a 24-week course of sofosbuvir (400 mg orally, daily) and ribavirin (1000–1200 mg orally, daily) with an assessment of cure (sustained virological response) at 12 weeks after completion of treatment (SVR12). Findings: Between June 6, 2015, and June 9, 2016, 4215 (89%) of 4721 eligible villagers were screened for HCV antibodies and HBsAg. Of these participants, 530 (13%) were HCV antibody positive and eight (<1%) were HBsAg positive. All HCV-antibody-positive individuals had an HCV-RNA assay, and 312 (59%) were HCV-RNA positive. All 312 completed a full baseline assessment with staging of liver disease, and 300 (96%) were given 24 weeks of sofosbuvir and ribavirin treatment within a median of 2·3 weeks (IQR 0·0–3·7) from serological diagnosis. 293 (98%) of the treated participants achieved SVR12. 42 (13%) HCV-RNA-positive participants had cirrhosis as determined by transient elastography, of whom 12 (29%) were diagnosed with hepatocellular carcinoma on the basis of α-fetoprotein measurement and ultrasound. 3575 (85%) of 4215 eligible villagers completed the baseline and after educational campaign survey, and awareness, knowledge, and adoption of safer practices to prevent HCV transmission all significantly increased (p<0·0001). Interpretation: This community-led educate, test-and-treat demonstration project achieved high uptake of HCV testing, linkage to care and treatment, and attainment of cure in one village, as well as awareness and adoption of practices to prevent transmission in the community. This approach could be an important strategy for adoption in rural settings to complement the national government programme towards the elimination of HCV in Egypt. Funding: Egyptian Liver Research Institute and Hospital.